Bagaimana Pelaksanaa Good Governance dalam Sistem Kesejahteraan Masyarakat Berkontribusi dalam Menciptakan Perdamaian Berkelanjutan: Sistem Kesejahteraan Denmark - Hutagaol, Kennedy Yeremia Alexander Abraham; Widodo, Pujo; Sitinjak, Halomoan Freddy; Sukendro, Achmed (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research is focused on peacemaking through welfare efforts using the Denmark welfare system model. Understanding the correlation of peace and welfare through Karl Marx’s theory. Welfare system is projected to ensuring the living quality of the citizen. However, not every country and its welfare system are able to bring result. Welfare system is a viable method in ensuring access to citizens, the functioning of the system however relies heavily in the government. The main purpose of the research is understanding how the good governance on welfare system contributes in creating a sustainable peace. The research method utilized in this research is the qualitative method, specifically the intrinsic case study method. Focusing and deep understanding of the specific case chosen. The data collected will be secondary data through literature studies. This research will use the concept of positive peace and good government as well as the human needs theoretical framework by Maslow. The writer argues that the Denmark welfare system is successful because of how the government is accountable and puts the people as the center of the idea, making the Denmark welfare system peaceful while also successful. The result of this research is that the government does achieve high rank in good governance, that the system is impactful, and that the system works in a cycle making it sustainably peaceful.